The insecticidal effects of different plant extracts on confused flour beetle, Tribolium confusum Jacquelin du Val, 1863 (Coleoptera: Tenebrionidae) - Güral, Yunus; Karaman, Erhan; Baydoğan, Gözde; Özgen, İnanç (My University, 2023)
This study was carried out to determine the insecticidal effects of different plant extracts on confused flour beetle, Tribolium confusum Jacquelin du Val, 1863 (Coleoptera: Tenebrionidae) and time-varying LD50 and LD90 values. LD50 and LD90 of the formulations were determined by the probit analysis method. The studies were conducted under controlled conditions in a climate cabin and air conditioning room at 25 ± 2°C and 60% humidity 2019 to 2020 in Fırat University Bioengineering Department in Turkey. In this study, Grainpro AITC-ALPHA (Monoterpen, Allyisothiocyanate,Cocoate methyl esters), Grainpro AITC-GAMMA (Gamma terpene, Allyisothiocyanate, Cocoate methyl esters-Eugenol), Grainpro GAMMA-EUG (Gamma terpinene, Eugenol, Cocoate methyl esters), and Grainpro AITC-EUC (Eucalyptus oil, Allyisothiocyanate, Cocoate methyl esters) plant formulations were used in doses (In all doses, different µL drug doses prepared in 1 ml were mixed in 1 liter of water and applied by obtaining 0.2 µL, 0.4 µL, 0.6 µL, 0.8 µL, 1 µL doses for each formulation). The two upper and two lower doses of the most effective drug obtained were then tested and their effectiveness was determined. It was determined that the insecticidal efficacy of the pesticides increased as the pesticide dose increased and two lower and two upper doses of the most effective dose of 1 µL were subjected to efficacy trials. Among these formulations, 1 µL and 1.10 µL doses of Gainpro AITC-EUC formulation were the most effective on the pest.
Keywords: Tribolium confusum; Plant extracts; Insecticidal effect; LD50; LD90